2022
DOI: 10.1177/10760296211072820
|View full text |Cite
|
Sign up to set email alerts
|

Arterial-renal Syndrome in Patients with ESRD, a New Disease Paradigm

Abstract: Background Patients with end-stage renal disease (ESRD) often present with an increased risk of cardiovascular disease. Conditions of compromised cardiovascular health such as atrial fibrillation (AFIB) and peripheral arterial disease (PAD) may alter biomarker levels in a way that reflects worsening ESRD. This study profiled biomarkers and laboratory parameters of endothelium dysfunction in patients with ESRD, categorized by additional AFIB and PAD conditions. Methods Citrated blood samples were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“… 20 Regarding this, recent studies have shown that the levels of inflammatory biomarkers such as CRP, TNF-α, IL-1, and IL-6 are elevated in CKD and ESRD patients. 21 , 22 Furthermore, this elevation has also been shown to be associated with the progression of CKD to ESRD with higher rates of cardiovascular complications and mortality in this patient group. 23 In vivo experiments showed a significant increase of serum levels of proinflammatory cytokines in patients with type 1 CRS compared to those with acute HF without renal insufficiency which included IL-6, IL-18, MPO, and neutrophil gelatinase-associated lipocalin (NGAL).…”
Section: Discussionmentioning
confidence: 97%
“… 20 Regarding this, recent studies have shown that the levels of inflammatory biomarkers such as CRP, TNF-α, IL-1, and IL-6 are elevated in CKD and ESRD patients. 21 , 22 Furthermore, this elevation has also been shown to be associated with the progression of CKD to ESRD with higher rates of cardiovascular complications and mortality in this patient group. 23 In vivo experiments showed a significant increase of serum levels of proinflammatory cytokines in patients with type 1 CRS compared to those with acute HF without renal insufficiency which included IL-6, IL-18, MPO, and neutrophil gelatinase-associated lipocalin (NGAL).…”
Section: Discussionmentioning
confidence: 97%
“… 16 , 17 Furthermore, this elevation has also shown to be associated with the progression of CKD to ESRD with higher rates of cardiovascular complications and mortality in this patient group. 17 20 Interestingly, major improvements were observed at the levels of inflammatory biomarkers after kidney transplantation; this has indicated that inflammation is not only a cause but also a consequence in the development of a kidney disease and its associated complications. 21 Regarding this, several dialysis-related factors have been associated with persistent and low-grade inflammation in ESRD.…”
Section: Introductionmentioning
confidence: 99%